Railway ecology - Borda-de-Água, Luís (2017)
We have divided the book into two parts. The first aims at reviewing the main ideas and methods related to the identification, monitoring, and mitigation of railway impacts on biodiversity, with emphasis on wildlife mortality, barrier effects, biological invasions, and the effects of other railway environmental impacts such as noise and chemical pollution. The second part of the book provides a set of case studies from around the world that illustrate the impacts of railways on wildlife and ways to reduce those impacts. Reflecting the strong interest in the topic of wildlife mortality, four chapters focus on the patterns of mortality resulting from collisions with trains and railway structures, each of which suggests several mitigation measures to reduce such mortality.